From the end to the beginning: Obtaining and evaluation of flexible PVC produced via chemical recycling of post-consumer PET - Donnini Mancini, Sandro [UNESP]; Rodolfo Junior, Antonio; Barcellos Mattos, Beatriz [UNESP]; Hoshi Pinto, Luana Misae [UNESP]; Cardoso de Morais, Leandro [UNESP]; Parra Ribeiro, Rafael [UNESP] (SAGE Publications, 2025)
Di(2-ethylhexyl) terephthalate (DEHTP) is a promising substitute for dioctyl phthalate (DOP, banned in certain countries) as a polyvinyl chloride (PVC) plasticizer. This research endeavors to present findings about the synthesis of DEHTP through the depolymerization of polyethylene terephthalate (PET) with 2-ethyl-1-hexanol, the production and assessment of PVC formulated with this plasticizer, and a comparative analysis with PVC compounded using commercial plasticizers (DOP and DEHTP). Approximately 200 post-consumer PET bottles underwent chemical recycling under various conditions, leading to complete depolymerization (99%) following a six-hour reaction at 300°C. The plasticizers were characterized by infrared spectroscopy, 1H nuclear magnetic resonance spectroscopy, and gas chromatography coupled to mass spectrometry. The flexible PVCs were tensile and hardness tested and submitted to dynamic mechanical and thermogravimetric analyses. The resulting plasticizer exhibited properties analogous to commercial DEHTP, producing flexible PVC with even better properties. For instance, the activation energy of the dehydrochlorination reaction of the flexible PVC produced with DHETP from depolymerization was 3.3% to 16.2% higher than those produced with commercial plasticizers.
Keywords: diethylhexyl phthalate; open-loop recycling; Para-substitution; thermal degradation